Kohti pohjoismaista rajayhteistyötä: Pohjoisen länsirajan ylittävä toiminta ja sen sääntely Suomen itsenäistymisestä sotienjälkeiseen aikaan - Pekola, Sami (Pohjois-Suomen Historiallinen Yhdistys ry, 2022)
This article analyses the cross-border activities and their regulation at the Finnish-Swedish northern border from the independence of Finland to the aftermath of the second World War. The process of change over time is being studied by applying a diachronic analysis. Activities across state borders are rarely limited to regional or local context. It is thus important to connect the international and national developments of the era to the formation of Finnish-Swedish border and its regulations. In this article human communities, sovereign states, their borders and regulations are perceived as parts of socially constructed reality. Extensive historical understanding is thus essentially important when analysing the border not just as a static judicial fact but as a product of dynamic social process. The article argues that the historical development of borders is not linear and determined, but a multi-dimensional process, in which different developments can occur at a different pace and go in different directions: some simultaneous developments can lower the border, others can make it higher. Legislation and other norms are factors that steer the characteristics of the border, yet at the same time they are manifestations of broader political, societal and cultural variables that form the social reality. The article covers historical development paths between two transitional periods, which are often defined from the nation-state perspective. In this article it is argued that the independence of Finland as an aggregate level change did not bring a substantial difference to the everyday cross-border practices nor their regulation at the Finnish-Swedish northern border compared to the time of the Finnish autonomy. Finnish-Swedish relations hit the rock bottom after the independence of Finland due to severe territorial disputes over the Aland islands, for example. Furthermore, some Finnish activists arose claims to move the Finnish-Swedish border westwards to re-unite the allegedly oppressed Finnish speaking minority ...